Role of Candida albicans secreted aspartyl protease Sap9 in interkingdom biofilm formation. Issue 3 (14th January 2016) - Dutton, Lindsay C.; Jenkinson, Howard F.; Lamont, Richard J.; Nobbs, Angela H.
Abstract : The fungus Candida albicans colonizes oral cavity surfaces and is carried by up to 60% of human populations. Biofilm development by C. albicans may be modulated by oral streptococci, such as Streptococcus gordonii, S. oralis or S. mutans, so as to augment pathogenicity. In this study we sought to determine if the cell wall-associated secreted aspartyl proteinase Sap9 was necessary for hyphal adhesin functions associated with biofilm community development. A sap9 Δ mutant of C. albicans SC5314 formed biofilms that were flatter, and contained fewer blastospores and more hyphal filaments than the parent strain. This phenotypic difference was accentuated under flow (shear) conditions and in the presence of S. gordonii. Dual-species biofilms of C. albicans sap9 Δ with S. oralis, S. sanguinis, S. parasanguinis, S. mutans and Enterococcus faecalis all contained more matted hyphae and more bacteria bound to substratum compared to C. albicans wild type. sap9 Δ mutant hyphae showed significantly increased cell surface hydrophobicity, ∼25% increased levels of binding C. albicans cell wall protein Als3, and reduced interaction with Eap1, implicating Sap9 in fungal cell–cell recognition. These observations suggest that Sap9 is associated with protein–receptor interactions between fungal cells, and with interkingdom communication in the formation of polymicrobial biofilm communities. Abstract : This study shows that the fungus Candida albicans cell wall-associated Sap9 proteinase is required for control of hyphal filament formation and separation, and for regulation of mixed-species biofilm formation by C. albicans with oral Streptococcus bacteria.